GARP Correlates With Tumor-Infiltrating T-Cells and Predicts the Outcome of Gastric Cancer - Jiang, Sutian; Zhang, Yifan; Zhang, Xiaojing; Lu, Bing; Sun, Pingping; Wu, Qianqian; Ding, Xuzhong; Huang, Jianfei (Frontiers in Immunology, 2021)
Accepting the crucial role of the immune microenvironment (TME) in tumor progression enables us to identify targets and develop new therapies. Glycoprotein A repetitions predominant (GARP) plays a vital part in maintaining regulatory T cell (Treg)-mediated immune tolerance. The role of GARP in TME of gastric cancer is still worth exploring. We investigated public genomic datasets from The Cancer Genome Atlas and Gene Expression Omnibus to analyze the possible role of GARP and its relationship with TME of gastric cancer. Fluorescence-based multiplex immunohistochemistry and immunohistochemistry for T-cell immune signatures in a series of tissue microarrays were used to validate the value of GARP in the TME. We initially found that GARP expression was upregulated in gastric carcinoma cells, and diverse levels of immune cell infiltration and immune checkpoint expression were detected. Gene expression profiling revealed that GARP expression was related to the TME of gastric cancer. GARP upregulation was usually accompanied by increased FOXP3+ Treg and CD4+ T cell infiltration. In addition, GARP expression had positive relationships with CTLA-4 and PD-L1 expression in gastric cancer. Cox regression analysis and a nomogram highlighted that the probability of poor overall survival was predicted well by GARP or GARP+CD4+ T cell. Taken together, this research underlines the potential impact of GARP in regulating survival and tumor-infiltrating T-cells. In addition, the impact role of CD4+ T cell immune signatures in the prognosis can be clinically meaningful, thereby providing a new idea for the immunotherapeutic approach.